2013
DOI: 10.1021/jz401281r
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated 2D-IR Using Compressed Sensing

Abstract: A fundamental aspect of Fourier transform (FT) spectroscopy is the inverse relationship between frequency resolution and the maximum scanned time delay. In situations where essential chemical information is contained in spectral peak amplitudes rather than in their detailed shapes, it is possible to dramatically reduce the experimental acquisition time of time domain methods such as two-dimensional infrared (2D-IR) spectroscopy. By introducing compressed sensing to the analysis and experimental design of 2D-IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 42 publications
0
30
0
1
Order By: Relevance
“…45 Furthermore, it was shown that CS reconstruction can also be used to retrieve the 2D spectrum from a uniformly sampled subset of the full signal. 46 Other non-uniform sampling protocols, such as exponentially biased, radial, or Poisson-gap sampling, are successfully applied in multidimensional NMR. [47][48][49][50] They benefit from a priori assumptions on the approximate signal characteristics and use a dense sampling close to the origin of the time domain where the signal amplitudes are still large.…”
Section: Introductionmentioning
confidence: 99%
“…45 Furthermore, it was shown that CS reconstruction can also be used to retrieve the 2D spectrum from a uniformly sampled subset of the full signal. 46 Other non-uniform sampling protocols, such as exponentially biased, radial, or Poisson-gap sampling, are successfully applied in multidimensional NMR. [47][48][49][50] They benefit from a priori assumptions on the approximate signal characteristics and use a dense sampling close to the origin of the time domain where the signal amplitudes are still large.…”
Section: Introductionmentioning
confidence: 99%
“…Compressed sensing provides a mathematical framework to unify signal reconstruction techniques across a variety of disciplines and hence will enable algorithms that have been established as robust in applications such as astronomy to be readily implemented in, e.g., NMR spectroscopy. We can therefore expect sparse sampling techniques to become commonplace in all areas of spectroscopy research, indeed compressed sensing has recently been demonstrated for 2D Fourier transform infrared spectroscopy 71…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…The time needed to scan the laser pulses and acquire sufficient signal-to-noise can sometimes present an issue. This might be alleviated to some extent by using cutting edge techniques such as compressed sensing (15,16). One of the requirements for capitalizing fully on the 2DES method for implementing molecular logic is that signal generation pathways need to be deconvolved.…”
Section: The Challenge Of Nonlinear Logicmentioning
confidence: 99%